2007
DOI: 10.1183/09031936.00071007
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamically unstable pulmonary embolism in the RIETE Registry: systolic blood pressure or shock index?

Abstract: Patients with acute pulmonary embolism (PE) presenting with haemodynamic instability have the worst prognosis. However, what is understood by haemodynamic instability has not been clearly defined.The Registro Informatizado de la Enfermedad Tromboembólica (RIETE) is an ongoing registry of consecutive patients with symptomatic, objectively confirmed, acute deep vein thrombosis or PE. The present authors compared the predictive value of a systolic blood pressure (SBP) value of ,100 mmHg and ,90 mmHg and the shock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 33 publications
1
41
1
1
Order By: Relevance
“…3- 7 The combination of HR and SBP may be more powerful than either HR or SBP alone, because early stages of shock are also taken into account. Therefore, SI can be a good marker of pre-shock.…”
Section: Methodsmentioning
confidence: 99%
“…3- 7 The combination of HR and SBP may be more powerful than either HR or SBP alone, because early stages of shock are also taken into account. Therefore, SI can be a good marker of pre-shock.…”
Section: Methodsmentioning
confidence: 99%
“…По данным обсер-вационных исследований число таких больных, у раз-ных авторов, составляет от 4,2 до 18,5% [11][12][13][14]. Причем попытки расширить показания к примене-нию ТЛТ у больных с ТЭЛА оказались безуспешными.…”
Section: роль тромболитической терапии при современном лечении больныunclassified
“…14 The shock index (SI), defined as the heart rate divided by systolic blood pressure, is an independent prognostic model of 30-day mortality in patients with PE. 15 A multicenter study demonstrated that the SI had high sensitivity in identifying the subgroups of patients at low risk of mortality. 15 In a new approach, this index is used to speed up the triage of patients with suspected acute PE.…”
mentioning
confidence: 99%
“…15 A multicenter study demonstrated that the SI had high sensitivity in identifying the subgroups of patients at low risk of mortality. 15 In a new approach, this index is used to speed up the triage of patients with suspected acute PE. 16 If the SI is 1 and higher and right ventricular dysfunction (RVD) is present on an echocardiogram in PE patients in poor general condition, early thrombolytic treatment can be administered without imaging studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation